1991
DOI: 10.1111/j.1365-2826.1991.tb00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin Activates C‐Fos Expression in Hypothalamic Oxytocin and Corticotropin‐Releasing Hormone Neurons

Abstract: The effect of systemically-administered cholecystokinin octapeptide (CCK) on hypothalamic oxytocin, vasopressin, and corticotropinreleasing hormone neurons was studied by analysis of c-fos antigen expression in immunocytochemically-characterized neurons in the supraoptic and paraventricular nuclei. CCK (100 pglkg intraperitoneally) caused a marked increase in nuclear c-fos immunocytochemical staining, which peaked at 60 to 90 min after injection. C-fos expression was found in most magnocellular oxytocin neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
101
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(110 citation statements)
references
References 29 publications
9
101
0
Order By: Relevance
“…The biochemical coding and exact mapping of activated neurons in the PVN needs to be further characterized. Previous studies in rats showed that peripheral CCK activates oxytocinergic neurons in the PVN (62,63). The synergistic interaction between CCK and leptin may have physiological relevance.…”
Section: Discussionmentioning
confidence: 94%
“…The biochemical coding and exact mapping of activated neurons in the PVN needs to be further characterized. Previous studies in rats showed that peripheral CCK activates oxytocinergic neurons in the PVN (62,63). The synergistic interaction between CCK and leptin may have physiological relevance.…”
Section: Discussionmentioning
confidence: 94%
“…The neuronal excitation (see Renaud et al, 1987;Leng & Dyball, 1991) results in an elevation of plasma oxytocin concentrations, rising 5 min after CCK injection to about 50 pg ml-' above basal levels (Verbalis et al, 1986a,b; . Systemically administered CCK also activates centrally-projecting oxytocin neurones, which form one limb of a gastric reflex arc, and also corticotrophinreleasing factor (CRF) neurones, that results in the release of ACTH (Verbalis et al, 1991b;Kamilaris et al, 1992). The profile of neuronal activation in the hypothalamus following systemic administration of CCK has been studied using products of the immediate-early gene c-fos as a marker.…”
Section: Introductionmentioning
confidence: 99%
“…After 20 d of the second restricted-food process, rats were killed at the moment of food arrival to analyze c-Fos immuno-reactivity in the brain. Because c-Fos protein takes between 60 and 90 min to be expressed after the activation of a neuron (24), this time point reflects the neuronal activation during FAA, at least 60 min before expected food arrival.…”
mentioning
confidence: 99%